Associação da amicacina com EDTA na pseudotrombocitopenia em felinos - Engelmann, Ana Martiele (2019)
Pseudothrombocytopenia (PTP) consists in a false decrease of platelet counts, is a phenomenon that occurs in vitro, resulting from platelet activation and consequent agglutination secondary to laborious venipuncture, inadequate blood storage or blood exposure to anticoagulant. Physiologically, felines platelets have particularities that make them more reactive and prone to agglutination. The presence of these platelet aggregates interferes with platelet counts by automatic counters and manual methods. The use of aminoglycoside amikacin in association to ethylenediamine tetraacetic acid (EDTA) has been shown to be efficient in preventing platelet aggregates in cases of PTP in humans. In this sense, the aim of this study was to evaluate the efficacy of amikacin, associated with EDTA, in the prevention of platelet aggregates in feline blood samples and to investigate its possible effects on hematological parameters. For this, was collected 1mL of blood from 100 healthy cats, 0.5mL stored in tubes with EDTA (EDTA group) and 0.5ml in tubes with EDTA and 10μL amikacin (EDTA-AMK group). The samples were processed in an impedance automated device to obtain the platelet count and other hematological parameters. Blood smears were also made in order to verify the presence of platelet aggregates. The presence of platelet aggregates was found in 56% of the EDTA group samples, in EDTA-AMK group, this percentage was only 5%. In the analysis of the 56 samples that presented platelet aggregates in the blood smear, there was a statistical difference (p<0.05) for the EDTA-AMK group in relation to the EDTA group, with a reduction in red blood cells count (RBC), hemoglobin (HGB), hematocrit (HCT), mean corpuscular volume (MCV) and total white blood cells count (WBC), as well as increased mean corpuscular hemoglobin (MCHC), platelet count (PLT) and plateletcrit (PCT). The proportions of the changes in these hematimetric indexes with the use of amikacin are, on average, not very expressive for RBC (-1.73%), HGB (-1.89%), HCT (3.82%), MCV (2.12%) and MCHC (2.02%). However, the mean changes in the results with the addition of this aminoglycoside were 47.73%, 53% and -17.70%, respectively, for PLT, PCT and for WBC. In the comparison of the 44 samples from the EDTA group in which the platelet aggregates were not observed, with the corresponding samples from the EDTA-AMK group, similar results were obtained regarding the influence of this aminoglycoside on the parameters evaluated. However, the differences in the PLT, PCT and WBC in the EDTA-AMK group in relation to the EDTA group were proportionally less representative (18.23%, 19.69% and -9.34%) in the samples without the identification of platelet aggregates than in those in which they were observed. Then, the addition of amikacin has been shown to be effective in preventing platelet aggregates in feline blood samples, thus increasing the accuracy of both platelet count and total leukocytes. In view of these results, the use of this drug can be recommended in the laboratory routine in order to increase the accuracy of the results of the platelet and leukocyte counts of felines blood samples destined to perform the blood count.